2010
DOI: 10.1093/ejechocard/jeq017
|View full text |Cite
|
Sign up to set email alerts
|

Sequential changes in myocardial function after valve replacement for aortic stenosis by speckle tracking echocardiography

Abstract: Myocardial function significantly recovers after replacing the stenosed aortic valve. However, there is a considerable difference between the response of longitudinal, radial, and circumferential function. Our data suggest that echocardiographic assessment of regional function is feasible and of potential clinical importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 18 publications
7
32
0
Order By: Relevance
“…In our patients, the compensated group exhibited values above the cutoff point, whereas in the decompensated group with and without CAD, values were 13.5% and 13.6%, respectively. Other authors demonstrated that SGLS returned to normal values at 1 year post valve replacement [44]; in our study SGLS values returned to normal only in the compensated group (Table 2).…”
Section: Discussionsupporting
confidence: 55%
“…In our patients, the compensated group exhibited values above the cutoff point, whereas in the decompensated group with and without CAD, values were 13.5% and 13.6%, respectively. Other authors demonstrated that SGLS returned to normal values at 1 year post valve replacement [44]; in our study SGLS values returned to normal only in the compensated group (Table 2).…”
Section: Discussionsupporting
confidence: 55%
“…However, significant amelioration also occurred in the apical segments after 12 months, which indicates constant long-term recovery of systolic function from the basis to the apex. 31 In addition, we detected regression of LVM, which further indicates favourable reverse remodelling. 31 …”
Section: Discussion Systolic Functionsupporting
confidence: 52%
“…31 In addition, we detected regression of LVM, which further indicates favourable reverse remodelling. 31 …”
Section: Discussion Systolic Functionsupporting
confidence: 52%
“…21,25,26) Interestingly, LSr decreased 6 months earlier than RSr, although LVEF was preserved during the one-year observation period. 21) Vinereaunu, et al suggested that a progressive decline in longitudinal systolic function is closely associated with global diastolic function, and the augmentation or preservation of radial contraction maintains normal ejection fraction.…”
Section: -7)mentioning
confidence: 91%